Efektivitas Digital Marketing Produk Cicil Emas Pada Bank Syariah Indonesia - Cholilah, Aprilinda Ummi; Haryanti , Peni (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
Digital marketing is an important element in sharia banking marketing, including gold installment products. This article aims to analyze the effectiveness of the digital marketing strategy for gold installment products at Bank Syariah Indonesia (BSI) KCP Mojokerto Surodinawan. This research uses a qualitative descriptive method with a case study approach. Data was collected through interviews with banks as well as secondary data in the form of relevant literature and annual reports. The research results show that the digital marketing strategies implemented, such as marketing via social media, the BSI Mobile application, educational content, and email marketing, have proven effective in reaching a wider audience, increasing interaction, and optimizing marketing costs. Social media is the main platform for conveying information, while the BSI Mobile application provides easy access for customers. Nevertheless, challenges such as increasing people's digital literacy and industrial competition remain the focus of improvement. It can be concluded that the implementation of innovative and data-based digital marketing strategies plays a significant role in supporting the growth of gold installment products in accordance with sharia principles.